The Julia G. Alexander collection of Alexander and Graham family papers - Alexander, Deborah; Alexander, Dicks; Alexander, Sarah Ann Graham, 1807-1839?; Graham, Hepzibah; Graham, James, 1773-1829.; Graham, Jane Maria, 1796-; Graham, Joseph, 1759-1836.; Graham, William Grenville, 1794-1827.
Chiefly correspondence and notebook of Sarah Ann Graham Alexander, teacher of New York (State) and Tennessee. Includes correspondence and other papers of Dicks Alexander and his wife Deborah Alexander, Hepzibah Graham, James Graham, his daughter Jane Maria Graham, Joseph Graham, William Grenville Graham, and William Grenville Graham. Correspondents include Andrew Jackson, Thomas A.R. Nelson, and J.R. Peters.
In part, negative photostats of originals in private hands.
Collection material in English.
Keywords: Jackson, Andrew, -- 1767-1845 -- Correspondence; Nelson, Thomas A. R. -- Correspondence; Peters, J. R. -- Correspondence; Alexander family; Graham family; New York (State) -- Social life and customs; Tennessee -- Social life and customs; Educators